Executive Committee Minutes 2011-11-17 - Academic Senate:::::::::
Agenda approved. Minutes of 11/3/11 approved. Chair Report. President Report. EPC Report. Provost Report. Associated Students Report. Budgeting Principles in Academic Affairs. Statewide Senator Report. Chair-Elect Report. Vice President of SAEM Report. APC Report. FSAC Report. Faculty Retreat. Senate agenda approved.